Putting risk in its proper place - Louis Eeckhoudt; Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper examines preferences towards particular classes of lottery pairs. We show how concepts such as prudence and temperance can be fully characterized by a preference relation over these lotteries. If preferences are defined in an expected-utility framework with differentiable utility, the direction of preference for a particular class of lottery pairs is equivalent to signing the nth derivative of the utility function. What makes our characterization appealing is its simplicity, which seems particularly amenable to experimentation.
Keywords: D81; 330; properness; prudence; risk apportionment; risk aversion; stochastic dominance; temperance; utility premium; Risikoaversion; Risikopräferenz; Erwartungsnutzen; Theorie